Beyond Rhetoric to Understanding Determinants of Wind Turbine Support and Conflict in Two Ontario, Canada Communities. (March 2014) - Walker, Chad; Baxter, Jamie; Ouellette, Danielle
The literature concerning local opposition to wind turbine developments has relatively few case studies exploring the felt impacts of people living with turbines in their daily lives. Aitken even suggests that such residents are subtly or overtly cast as deviants in the current literature. Our mixed-methods, grounded-theory case study of two communities in Ontario, Canada provides insights about such residents though twenty-six face-to-face in-depth interviews, 152 questionnaires, and basic spatial analysis involving locals who have been living with operating turbines for several years. Despite being neighbours the communities differ on several measures including the spatial clustering of turbines. Opposition is significantly predicted by: Health, siting process, economic benefits, and visual aesthetic variables. Though a majority supports the turbines we focus on the interplay of that majority with those experiencing negative impacts, particularly related to health. We highlight an asymmetry of impacts at the local level on those who oppose turbines, which is supported by rhetorical conflict at multiple scales. The findings point to the need for greater attention to mitigating impacts, including conflict, by understanding how siting policies interact with social processes at the local level.